Ancient Maya impacts on the Earth's surface: An Early Anthropocene analog?. (15th September 2015) - Beach, Tim; Luzzadder-Beach, Sheryl; Cook, Duncan; Dunning, Nicholas; Kennett, Douglas J.; Krause, Samantha; Terry, Richard; Trein, Debora; Valdez, Fred
Abstract: The measure of the "Mayacene, " a microcosm of the Early Anthropocene that occurred from c . 3000 to 1000 BP, comes from multiple Late Quaternary paleoenvironmental records. We synthesized the evidence for Maya impacts on climate, vegetation, hydrology and the lithosphere, from studies of soils, lakes, floodplains, wetlands and other ecosystems. Maya civilization had likely altered local to regional ecosystems and hydrology by the Preclassic Period (3000-1700 BP), but these impacts waned by 1000 BP. They altered ecosystems with vast urban and rural infrastructure that included thousands of reservoirs, wetland fields and canals, terraces, field ridges, and temples. Although there is abundant evidence that indicates the Maya altered their forests, even at the large urban complex of Tikal as much as 40% of the forest remained intact through the Classic period. Existing forests are still influenced by ancient Maya forest gardening, particularly by the large expanses of ancient stone structures, terraces, and wetland fields that form their substrates. A few studies suggest deforestation and other land uses probably also warmed and dried regional climate by the Classic Period (1700-1100 BP). A much larger body of research documents the Maya impacts on hydrology, in the form of dams, reservoirs, canals, eroded soils and urban design for runoff. Another metric of the "Mayacene" are paleosols, which contain chemical evidence for human occupation, revealed by high phosphorus concentrations and carbon isotope ratios of C4 species like maize in the C3 –dominated tropical forest ecosystem. Paleosol sequences exhibit "Maya Clays, " a facies that reflects a glut of rapidly eroded sediments that overlie pre-Maya paleosols. This stratigraphy is conspicuous in many dated soil profiles and marks the large-scale Maya transformation of the landscape in the Preclassic and Classic periods. Some of these also have increased phosphorous and carbon isotope evidence of C4 species. We synthesize and provide new evidence of Maya-period soil strata that show elevated carbon isotope ratios (δ 13 C), indicating the presence of C4 species in typical agricultural sites. This is often the case in ancient Maya wetland systems, which also have abundant evidence for the presence of several other economic plant species. The "Mayacene" of c. 3000 to 1000 BP was thus a patchwork of cities, villages, roads, urban heat islands, intensive and extensive farmsteads, forests and orchards. Today, forests and wetlands cover much of the Maya area but like so many places, these are now under the onslaught of the deforestation, draining, and plowing of the present Anthropocene. Highlights: The Ancient Maya left a richly variegated landscape of the Early Anthropocene. Ancient erosion truncated soils and buried sinks, leaving golden spikes in strata. They left positive impacts or landesque capital such in terraces and wetland fields. They lived through pluvials and droughts, perhaps exacerbating Late Classic drought. They left myriad adaptive features such as reservoirs and useful species still extant.